Engaging with colonial archives: reflections of an end-user - Olukoju, A (Vestiges: Traces of Record, 2016)
Official and/or public archives were a byproduct of colonial rule in Africa. (Archives are a byproduct of administrative governance everywhere.) Given the density and diversity of colonial archival records, historians have tended to rely on them for the study of the colonial period. Publications on the use of archives have not captured the perspective of end-users, who often face peculiar challenges in the use of colonial and metropolitan archives. This paper provides an end-user perspective on colonial archives in Nigeria and the United Kingdom. It highlights the challenges of data collection and prospects of optimal use of archival source material. The discussion is of general application to users of colonial archives especially in the former British colonies in Africa.